Societal Behavior Towards Islamic Insurance: A Sociological and Anthropological Perspective on Sharia Economic Law - Rumaf, Muh Anwar Nurhasan (Institut Agama Islam Negeri Metro, 2024)
Islamic insurance has become a popular investment choice among Muslim communities, as it offers a means to mitigate future risks. The success of Islamic insurance companies is closely linked to the community's understanding of the importance of Islamic insurance. This study aims to identify and analyze the factors influencing societal behaviour towards Islamic insurance from a sociological and anthropological perspective on Sharia economic law. The analytical methods include data reduction, fact presentation, and conclusion drawing. The study's findings indicate that the most significant factor influencing the decision to adopt Islamic insurance is the level of understanding of Sharia principles, followed by the quality of the products. However, indicators such as premiums and promotional activities are less known among respondents, suggesting that insurance companies must enhance their efforts to promote Islamic insurance to the public. This research provides a deeper understanding of the factors influencing societal behaviour towards Islamic insurance and offers relevant recommendations for developing effective marketing strategies for Islamic insurance in Indonesia from both sociological and anthropological perspectives.